Hindari Nomophobia pada Anak dengan Bermain Sambil Belajar - Fadhilla Triayu; Bengkel Ginting (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2023)
The emergence of cell phones/smartphones has made many children more fun and busy with the features on these devices, individuals prefer interaction via social media networks rather than having to meet face to face. The emergence of this smartphone also has a new effect on user behavior, namely smartphone addiction behavior or a person's dependence on the continuous use of a smartphone without considering the negative impact. Cellphone/smartphone addiction is a form of attachment or addiction to cell phones that may become a social problem such as withdrawal, and difficulties in performing daily activities or as a disorder of impulsive control over one's self. This is also experienced by the people in the Kedai Durian Village. Children in this community think that playing smartphones for long periods of time is a natural thing to do. Therefore, the assistance process will be carried out in PKL 2 activities using the groupwork method with stages consisting of Intake, Assessment and Intervention Planning, Member Selection, Group Development, Evaluation and Termination. The focus of the completion that will be carried out is by getting used to doing positive activities such as drawing, painting, making handicrafts. This is done as a strategy to get rid of smartphone addiction. This goal was declared successful because the children had started to be interested in doing positive activities by drawing with their friends instead of playing on smartphones.